Analisis Implementasi Pendidikan Karakter Pada Peserta Didik Kelas V SDN Wanoja 02 Kabupaten Brebes Jawa Tengah - Sifa Afiatul Laeli; Cece Rakhmat; Fajar Nugraha (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study aims to determine the implementation of character education in fifth grade students at SDN Wanoja 02 Brebes Regency, Central Java. This study aims to describe and analyze the implementation of character education in class V students at SDN Wanoja 02. Based on the research results, it was found that the implementation of character education in class V students at SDN Wanoja 02 in learning activities and outside learning activities is carried out in various ways. The implementation of character education in learning is implemented through five models, namely habituation, learning methods, conditioning, exemplary, and providing motivation, advice, understanding, and appreciation. Meanwhile, the implementation of character education outside of learning activities is implemented through habituation, provision of school programs, exemplary, and provision of motivation and appreciation.